Who Commits Terrorism Alone? Comparing the Biographical Backgrounds and Radicalization Dynamics of Lone-Actor and Group-Based Terrorists - Schuurman, Bart (Crime & delinquency, 2025)
Why does one person radicalize to involvement in terrorist violence within a group-based context, while another engages in this form of violence alone? Existing research remains subject to limitations related to sample size, ideological and geographical range, and contradictory findings. This article draws on a newly-developed dataset to compare group-based and lone-actor terrorists across a range of predictors. Statistically significant bivariate associations and regression analyses suggest that lone actors have fewer criminal antecedents and lower exposure to social settings that enable group-based participation in terrorism. Limited perceived social skills and high social isolation may inhibit their ability to join terrorist groups. Lone actors also have little experience with non-violent activism, and tend to radicalize at a later age.